Microscopic investigation of pollen morphology of Brassicaceae from Central Punjab‐Pakistan. Issue 4 (6th January 2020) - Amina, Hafiza; Ahmad, Mushtaq; Bhatti, Ghulam Raza; Zafar, Muhammad; Sultana, Shazia; Butt, Maryam Akram; Bahadur, Saraj; Haq, Ihsan‐Ul; Ghufran, Muhammad Asad; Lubna; Ahmad, Shafiq; Ashfaq, Shomaila
Abstract: The intention of the current study is to provide an account on the palynological features of Brassicaceae from Central Punjab‐Pakistan as a basis for future studies. Different morpho‐palynological characteristics both qualitative and quantitative were analyzed during this research which includes shape of pollen, diameter of pollen, P/E ratio, exine sculpturing, thickness of exine, type of pollen, shape and size of lumens, and thickness of murus. Taxonomic keys were also constructed based on pollen morphological characters for correct identification of species. This study aims to provide detailed information of pollen diversity and their exine structure based on both qualitative and quantitative characters by using Light microscopy and Scanning electron microscopy. Shape of pollen is mostly prolate, but some species also have sub‐prolate to spheroidal prolate types. Exine ornamentation in most species was reticulate, whereas micro reticulate (one species) and coarsely reticulate (one species) exine also observed in some pollen. All the pollen mentioned in this study have tricolpate apertures. Variation found in thickness of exine and other characters proved to be helpful at generic and specific level. The results reinforced the significance of pollen morphological features of family Brassicaceae and aid for valuable taxonomic tool in plant systematics. Abstract : First documentation of pollen morphology of Brassicaceae from Central Punjab‐Pakistan. Application of Scanning Electron Microscopy to highlight the pollen morphological features of Brassicaceae. Formulation of taxonomic key to focus variations among studied taxa in terms of pollen morphology.